Discrimination as a Global Paradigm: United Kingdom and United States of America in Focus - Mendy, Ousu (Lampung Journal of International Law, 2023)
Despite the international community's commitment to protecting human rights, Equality before the law remains a global problem. This research offers a global perspective on the current threat odiscrimination emerging from the paradigm shift from Equality before the law as a universal principle declared in the Universal Declaration of Human Rights. This normative research explored extensive theoretical approaches based on secondary data, including journal articles, books, and international conventions. The results of this research showed that the current democratic system is experiencing a setback due to different factors that include autocracy and unconstitutional change of governments through coup d' état. The impact odiscrimination on inequality is destructive. Women have also made significant progress in many areas over time in places wherdiscrimination is low, enabling them to close the gender gaps.